Gender, Religion and Workplace: Reimagining Reasonable Accommodation - Narain, Vrinda (Canadian Labour and Employment Law Journal, 2017)
This paper evaluates the potential of the framework of reasonable accom- modation under Canadian human rights legislation to respond adequately to the workplace discrimination claims of minorities, particularly racialized Muslim women. Developing the premise that religious freedom and gender equality are not mutually exclusive, the author considers the legislative and judicial context of multiculturalism in Canada, as exemplified by the R. v. NS case (dealing with whether a witness in legal proceedings may wear a niqab while testifying) and by certain legislative initiatives (such as the federal Zero Tolerance for Barbaric Cultural Practices Act and the Quebec Charter of Values) that reflect a climate of growing xenophobia and islamophobia and that reinforce the "otherness" of minority racialized women under the pretext of secularism and gender equality. The paper then examines more closely the existing legal framework for rea- sonable accommodation in the workplace, arguing that the rigorous standard adopted by the Supreme Court in Meiorin was weakened and devalued in subse- quent decisions such as McGill and Hydro-Qu6bec. Ultimately, the author con- tends, state multiculturalism should be challenged and reconceptualized through the prism of critical multiculturalism, in order to move away from a simplistic emphasis on cultural difference and to address the underlying systemic issues of racism and discrimination. Furthermore, she argues, the notion of reasonable accommodation should be reformulated to shift the focus away from accommo- dation of minority women as tolerated exceptions to the norm, and towards the achievement of substantive equality through structural change.